2019
DOI: 10.1039/c9ce00631a
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the vertical orientation of two-dimensional perovskites

Abstract: Factors determining the orientation of two-dimensional perovskites were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…It should be noted that our films were too thin compared to the photoactive layer employed in photovoltaics. The small thickness could limit the growth of vertically standing phases converted from stable intermediate complexes, unlike the thick films in which phases can be perpendicularly oriented by slow crystallization …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that our films were too thin compared to the photoactive layer employed in photovoltaics. The small thickness could limit the growth of vertically standing phases converted from stable intermediate complexes, unlike the thick films in which phases can be perpendicularly oriented by slow crystallization …”
Section: Resultsmentioning
confidence: 99%
“…We propose that the stability of intermediate complexes can be a factor in controlling the orientation of crystal phase. It is worth mentioning that our thin films were deposited by antisolvent (chlorobenzene) dripping during spin‐coating in a water‐free environment, because those can also affect phase orientation . The previous studies reported that for large‐ n phases, the orientation of the perovskite seeds produced at the interface with atmosphere strongly influences that of the phases in the resulting films .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studying the crystallization kinetics of 2D perovskite is curial to effectively control the film forming process and adjust the crystal orientation (perpendicular to the substrate), which can effectively avoid or reduce the adverse effects of the organic molecular layer and improve device efficiency. [ 47,48 ] Nevertheless, few review articles were published on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] The desired average crystallographic orientation of (quasi-) 2D perovskite films can, to a large extent, be obtained through tuning of the deposition process, for example, by tuning the deposition temperature, atmosphere, or chemical composition of the precursor solution. [11,20,[26][27][28] In addition to the average crystallographic orientation, the microstructure of perovskite films has a marked impact on its optoelectronic properties. An increase in the average grain size, for instance, is often associated with increased device performance due to a reduction of trap-assisted recombination at grain boundaries.…”
mentioning
confidence: 99%